Study and simulation of Sparse Code Multiple Access (SCMA) for 5G New Radio - عاد, مريم (university of Eloued جامعة الوادي, 2019)
Today ,Researchers competing to make the best experience for users that is why they are always developing a new generation of networks, for example : in the fifth generation, they will transfer Multiple Access Schemes techniques from Orthogonal Multiple Access to Non Orthogonal Multiple Access to increase the number of user's. The new Multiple Access Schemes (Non-Orthogonal Multiple Access) have two dominant solutions : power domain and code-domain. In this work we are interested in about code domain called Sparse Code Multiple Access. Encoding SCMA based on codebooks design and we knew how it can be created in the Uplink system at Physical Resource Element Mapping blocks, this is the main our hypothesis. Also, we have known the main operation in these blocks: Factor Graph, Complex Constellation, Phase Rotation, Permutation Set. Finally, we have shown the importance of turbo code, compared with different SCMA demodulation algorithms and we have found the best between them is ‘stochastic’. يتنافس الباحثون اليوم على تقديم أفضل تجربة للمستخدمين ، ولهذا السبب دائمًا ما يطورون جيلًا جديدًا من الشبكات على سبيل المثال: في الجيل الخامس ، سينقلون تقنيات من الوصول المتعدد المتعامد الى الوصول المتعدد الغير متعامد وذلك لزيادة عدد المستخدمين . تمتلك تقنية الوصول المتعدد الغير متعامد نطاقين للحلول : باستخدام مستويات الطاقة مختلفة و باستخدام شفرات مختلفة . في هذا العمل نحن مهتمون بنطاق التشفير المسمى الترميز المتناثر متعدد الوصول (SCMA). الترميز SCMA يعتمد أساسا على تصميم دفاتر الترميز، وقد عرفنا كيف يمكن إنشاء هذا الترميز في نظام الإرسال في كتلة تعيين عنصر الموارد المادية (PRE Mapping) ، وهذه تعتبر فرضيتنا الرئيسية لهذا العمل. أيضا ، تعرفنا على العمليات الرئيسية في هذه الكتل . أخيرًا ، أظهرنا أهمية ترميز توربو ، وقمنا بإجراء مقارنة مع مختلف الخوارزميات لفك تضمين باستعمال ترميز SCMA ووجدنا أن أفضلها هو ‘stochastic’.
مذكرة ماستر تخصص في انظمة الاتصالات
Keywords: 5G ; UP; MAS; OMA; NOM; SCMA; PRE .; الجيل الخامس, الوصلة الصاعدة, الوصول المتعدد, الوصول المتعدد المتناظر, الوصول المتعدد الغير متناظر.